2005
DOI: 10.1172/jci23626
|View full text |Cite
|
Sign up to set email alerts
|

GPR109A (PUMA-G/HM74A) mediates nicotinic acid–induced flushing

Abstract: Nicotinic acid (niacin) has long been used as an antidyslipidemic drug. Its special profile of actions, especially the rise in HDL-cholesterol levels induced by nicotinic acid, is unique among the currently available pharmacological tools to treat lipid disorders. Recently, a G-protein-coupled receptor, termed GPR109A (HM74A in humans, PUMA-G in mice), was described and shown to mediate the nicotinic acid-induced antilipolytic effects in adipocytes. One of the major problems of the pharmacotherapeutical use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
277
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(299 citation statements)
references
References 52 publications
11
277
0
2
Order By: Relevance
“…Recently, it has been demonstrated that the receptor is also expressed on macrophages and dendritic cells, but not on monocytes. 4 Therefore, GPR109A receptors are expressed on some, but not all, leukocytes and may play a role in defense mechanisms against pathogens, at least within the innate immune system. NA binds to both low-(GPR109B; HM74) and high-affinity (GPR109A; HM74A) receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been demonstrated that the receptor is also expressed on macrophages and dendritic cells, but not on monocytes. 4 Therefore, GPR109A receptors are expressed on some, but not all, leukocytes and may play a role in defense mechanisms against pathogens, at least within the innate immune system. NA binds to both low-(GPR109B; HM74) and high-affinity (GPR109A; HM74A) receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that interferon-g is able to induce GPR109A receptors in macrophages, and that NA is subsequently able to stimulate prostaglandin E2 and D2 synthesis in these cells. 4 The identification of functional GPR109A receptors in a cell outside adipose tissue raised the question whether additional cell types carry GPR109A receptors, which might also be targeted during therapy with NA.…”
mentioning
confidence: 99%
“…Recent work has begun to elucidate the mechanism by which nicotinic acid induces flushing (16 -19). GPR109A has been shown to mediate nicotinic acid-induced flushing through release of prostaglandin D2 (PGD 2 ) and involves the activation of the DP1 receptor and possibly a PGE 2 receptor (EP2 or EP4) (16,18) Recent work has further supported the hypothesis that it is GPR109A receptors on Langerhans cells in the skin that mediate nicotinic acid-induced flushing through generation of PGD 2 (17,19).…”
mentioning
confidence: 99%
“…In man, the flush response to niacin can be completely abolished by COX inhibitors such as aspirin or indomethacin (Svedmyr et al, 1977;Wilkin et al, 1982). In mice, the flush response to niacin can be eliminated by knocking out genes for either the niacin receptor or COX-1, consistent with an exclusive and obligatory role for this pathway in niacin-evoked skin flushing (Benyó et al 2005). Classical vasodilatory mediators, such as histamine, bradykinin, serotonin, and acetylcholine do undergo changes in their skin transudate levels after niacin challenge (Morrow et al, 1992;Plummer et al, 1977).…”
Section: Mediation Of Niacin Flush By Aa Metabolitesmentioning
confidence: 99%
“…Formation of AA is the rate-limiting step in the biosynthesis of the vasodilatory PGD 2 and E2 (PGE 2 ) (Murakami and Kudo 2004) These prostaglandins bind to specific prostanoid receptors on vascular smooth muscle within the skin. Activation of prostanoid receptors dilates cutaneous blood vessels (Lai et al, 2007), and a visible skin flush arises from the ensuing increased blood flow (Benyó et al, 2005;Maciejewski-Lenoir et al, 2006;Morrow et al, 1989Morrow et al, , 1992.…”
Section: Mechanism Of the Niacin Flush Responsementioning
confidence: 99%